Infecção experimental de bezerros com recombinantes do herpesvírus bovino tipo 5 com deleções nos genes da glicoproteína e, timidina quinase e ambos - Santos, Cyndia Mara Bezerra dos (2010)
Bovine herpesvirus type 5 (BoHV-5) is the etiologic agent of neurological disease in calves. The use of recombinant differential vaccines have been proposed against the disease. This dissertation relates an investigation on the attenuation in calves of three BoHV-5 recombinants with deletions in the coding regions of glycoprotein E (BoHV-5gEΔ), thymidine kinase (BoHV-5TKΔ) or both (BoHV-5gETKΔ) for potential use in vaccines. Each of the four groups of calves was inoculated intranasally with one of the mutants or the wild type virus (wt [SV507/99]) and monitored thereafter. The calves inoculated with wt virus shed virus for an average of 12.3 days (106.8DICC50/mL), in the group BoHV-5gEΔ for 11 days (105.1DICC50/mL), in the group BoHV-5TKΔ for 9.6 (105.9DICC50/mL) and in the group BoHV-5gETKΔ for 6.2 days (104.7DICC50/mL). No respiratory or systemic signals were observed in animals inoculated with the recombinants, while two calves of the wt group presented neurologic disease and were euthanyzed in extremis. Seroconversion was verified on the 32 days post-inoculation (pi) in all animals of group wt and BoHV-5gEΔ, while 2 and 4 animals of the groups BoHV-5TKΔ e BoHV-5gETKΔ seroconverted, respectively. Aiming at reactivating latent infection, on the 42 days pi, animals were treated with dexamethasone (Dx). Reactivation was achieved in wt group while groups BoHV-5gE and BoHV-5TKΔ shed virus only for one or two days. No virus shedding was verified on group BoHV-5gETKΔ. Euthanasia was executed 30 days later and brain sections were collected for DNA viral detection. Viral DNA was detected in the brain of wt inoculated animals and in restricted brain sections in the BoHV-5gEΔ group. These results demonstrated that mutants are fully attenuated for calves during acute infection and present a reduced ability to establish and/or reactivate latent infection after Dx administration. Therefore these recombinants may be useful in vaccine formulations.